The effect of physical activity, pharmacologic interventions, over-the-counter supplements and cognitive training in preventing Alzheimer’s disease, mild cognitive impairment and related dementias: an overview - Navickaitė , G. (Neurologijos seminarai, 2018)
Due to the aging population, the incidence of Alzheimer’s disease and related dementias (ADRD) and mild cognitive impairment (MCI) is likely to increase. Currently, there is no hard evidence neither on effective methods of their treatment nor on even prevention. However, the potential benefits of physical activity, pharmacologic interventions, over-the-counter supplements and cognitive training are publicly discussed. Nonetheless, positive effects of such methods are not based on the evidence obtained from the related studies. This article presents an overview of the results of systematic analyses of the four methods – physical activity, pharmacologic interventions, over-the-counter supplements and cognitive training – and their effect in preventing ADRD and MCI.
Keywords: Alzheimer’s disease; dementia; mild cognitive impairment; physical activity; pharmacologic intervention; over-the-counter supplements; cognitive training